The Students’ Perception of Teacher Teaching Multipurpose Media At SMP N 2 Lampasio - Asrul Safrudin; Indah Indrawati; Ismail Yunus H (Universitas Insan Budi Utomo, 2025)
This study aim ed to determine (1) the types of multipurpose media used by the teacher in teaching English ; (2) The students’ perception of the media used by teacher in teaching English.The Data collection was conducted from July to August 2024 of 10 students of class VIII of SMP N 2 Lampasio from two classes. This study used a descriptive qualitative research method, the instruments used are documentations and interviews. The Documentations was used to obtain evidence of the media used by the teacher in class VIII of SMP N 2 Lampasio and interviews were conducted with students of class VIII. The results of the study showed that the types of multipurpose media used by the teacher in teaching English were 1.whiteboard, 2.English books, 3.dictionaries, 4.modules,and 5.cardboards. The total respondents of this study were 11,consisting of 1 English teacher and 10 students. The result of the student interviews showed that most students given positive perceptions of the media used by the English teacher in the teaching process based on the 3 indicators used, the first indicator is absorption of stimuli,in this indicator the results obtained are that students felt happy, more enthusiastic and active, more enthusiastic in learning English. The second indicator is understanding or comprehension of the object, in this indicator it is found that students easier to understand the material, they benefited from teaching media, helped students in teaching English,and the last indicator is individual assesment or evaluation of the object,in this indicator students felt confident, helped in students’ creativity and motivation, and attracted students’ attention. Meanwhile, there are also some students who give negative perceptions toward the media used by English teacher in teaching process, namely they cannot pronounce words correctly or lack of student vocabulary, there is a feeling of boredom due to the continuous use of the same teaching media and the class conditions which are sometimes noisy.